MOTIVASI KERJA ANGGOTA POLISI BERDASARKAN GAYA KEPEMIMPINAN DAN LINGKUNGAN KERJA - M. Aqsa Pradipta; Kayla Rahayu Putri, Eha Amelya Suherman, Sesya Surya Safira, Tugimin Supriyadi (Jurnal Salome : Multidisipliner Keilmuan, 2024)
The police play an important role in the life of the state. In general, the police's job is to maintain peace, maintain tranquility, protect the state, protect the community, and be ready if the community experiences difficulties. Currently, there are many cases of police officers whose work is no longer in line with what the community and their organization expect. The aim is to determine the motivation of police officers for their performance which includes leadership style and work environment. The method we used in preparing this research was Library Research. Data collection uses the Google Scholar search engine to obt ain data. The research results show that motivation, leadership style, and work environment are very important for police performance. Motivation helps utilize resources and maintain stability, while leadership style motivates performance through rewards and recognition. A conducive work environment also influences performance by 63.7%.